(untitled) (Research, Society and Development, 2022)
Neurological disorders and cognitive impairment are commonly associated with HIV. Although severe and progressive neurocognitive impairment has become rare in infectious disease clinics in the era of potent antiretroviral therapy, the majority of HIV patients worldwide perform below expectations on formal neurocognitive tests. Objective: To demonstrate the effects of HIV associated with neurocognitive impairment. Method: This is an integrative literature review that followed the PICO strategy to identify factors associated with HIV-related Neurocognitive Disorder. The search for articles was carried out in three electronic databases: Medline, Lilacs and Scielo. The descriptors “AIDS Dementia Complex”, “HIV”, “Long-Term HIV Survivors”, “Dementia”, “Neurocognitive Disorders”, with full texts, published from 2012 to 2022, in English, Portuguese and Portuguese, were used. Spanish and the Boolean operator AND was used. Result: 356 articles were found. Twenty-five articles were selected to be read in full and 5 met the criteria of this review. Conclusion: Comorbidities contribute to impairment, but are insufficient to explain the frequency of impairment found. HIV disease markers, such as current viral load and CD4 count, are not more strongly associated with continued commitment to therapy, while cardiovascular disease markers and inflammatory markers appear to be more associated. Novel cerebrospinal fluid and neuroimaging biomarkers are needed to detect and follow up on impairment. Ongoing research to optimize HIV therapy in the central nervous system, and potentially intervene in downstream neurotoxicity mechanisms remain important avenues for future investigation. Ultimately, total control of the virus in the brain is a necessary step towards the eradication of HIV.